Research Software Engineering in the Energy Domain as Part of NFDI4Energy - Seiwerth, Corinna; Niebisch, Michael; Ferenz, Stephan; German, Reinhard (Conference for Research Software Engineering in Germany, 2024)
Research software presents an important research artifact in energy research. Therefore, the National Research Data Infrastructure for the Interdisciplinary Energy System Research (NFDI4Energy) addresses the handling of research software across the entire research and transfer cycle within energy system research projects. For this, the FAIR data principles are applied not only to data but also to softwar